Ayurvedic Management of Diabetic Complications - A Case Report - Subash, P Suparya; Giri, P V (International Research Journal of Ayurveda & Yoga, 2023)
Diabetes mellitus can fall under Prameha in Ayurveda. Long-standing Prameha leads to several complications. Some of the subsequent complications of diabetes mellitus are diabetic osteomyelitis, charcot foot, peripheral neuropathy, diabetic ulcer, periarticular arthritis, etc. This case will be discussing a patient who had some of the above complications. Diabetic complications were badly affecting his day-to-day activities. Hence, the treatment was mainly focused on reducing his symptoms. 73-year-old upper-middle-class man resided at Vijayawada for the past 70 years and worked as a businessman (egg cellar) for 50 years there, admitted to Vaidyaratnam Ayurveda College hospital on 2020 January 21st, presented with numbness of both upper limbs and lower limbs and difficulty in walking for the past 2 years and difficulty to raise left upper limb for the past 1 year. The case was diagnosed as Prameha Upadrava. Accordingly, the basic Ayurvedic principles were used for the treatment. Along with internal medicines, Rookshana, Snehana, Swedana, Sodhana, Rasayana, and Samana therapies were also administered. After 47 days of treatment, he was able to walk without moving to one side like he used to. He was also relieved of tremors and the numbness had begun subsiding. His left shoulder joint flexion and abduction were possible up to 120*. This case categorically emphasizes the need for positively constructive and effective results if two systems of medicine go hand in hand at different stages of treatment to achieve optimum healing of the patient. This case also tells us the importance and effectiveness of Rasayana therapy in Prameha.